New Documentary Ecologies
XII, 254 p.
Keywords: Providing a unique collection of perspectives on the persistence of documentary as a vital and dynamic media form within a digital world, New Documentary Ecologies traces this form through new opportunities of creating media, new platforms of distribution and new ways for audiences to engage with the real.